Teachers' Views about the Characteristics of Pedagogical Talents - Orgoványi-Gajdos Judit; Kovács Edina (Sciendo, 2020)
Introduction:This paper presents the results of a survey on excellent teachers conducted in Hungary in 2018. The main question of the study was how pedagogical talents can be characterised by competences and personality traits according to effective teachers and their colleagues. Furthermore, what effective teachers think about their own competences and characteristics, as well as how that is related to their beliefs of pedagogical talents was tested.